Tort liability for sexual harassment - Sardar Baig, Farheen Baig; Ali Mohamed, Ashgar Ali (2015)
Sexual harassment conducts such as patting, pinching, constant brushing or touching an inappropriate area of another person's body, making sexually related comments, jokes and graphic drawing, degrading comments on one’s appearance, displaying sexually suggestive pictures, amongst others, are examples where the honour and dignity of an employee is violated. Such conducts if goes unchecked, would create ‘intimidating, hostile and offensive work environment which can adversely affect the industrial relations climate in the organisation’. In most cases, the victims get annoyed, angry and even embarrassed by the unwanted sexual attention, as it belittles their persons. The aggrieved worker may experience emotional trauma, anxiety, nervousness, depression and feeling of low self-esteem. Further, it may also affect the employee's morale and job performance such as difficulty in concentrating on their job. An employer may avoid liability if they exercised reasonable care to prevent or correct promptly any harassing behaviour. If a co-worker is involved, the employer is generally liable if it knew or should have known of the misconduct, unless it can show that it took immediate and appropriate corrective action. Further, a failure to respond to bona fide complaints of sexual harassment would constitute a breach of the implied trust and confidence term. In the aforesaid breach, the aggrieved employee may walk out of her job and claim constructive dismissal. This paper would explore the possible cause of action in tort against the assailant for general and specific damages for the alleged assault and battery arising from the unwelcomed incidents of sexual harassment.